2013
DOI: 10.3171/2013.3.jns122214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular oncogenesis of craniopharyngioma: current and future strategies for the development of targeted therapies

Abstract: Abbreviations used in this paper: TCF = T cell-specific transcription factor; VEGF = vascular endothelial growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 95 publications
2
23
0
Order By: Relevance
“…Histologically, these tumors are classified as WHO grade I tumors, and they are subdivided into an adamantinomatous type arising from odontogenic cells (mostly in pediatric patients) or a papillary type arising from buccal mucosa rests (mostly occurring in adults) [3]. Despite their benign histological appearance, their prognosis remains uncertain and may often be unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, these tumors are classified as WHO grade I tumors, and they are subdivided into an adamantinomatous type arising from odontogenic cells (mostly in pediatric patients) or a papillary type arising from buccal mucosa rests (mostly occurring in adults) [3]. Despite their benign histological appearance, their prognosis remains uncertain and may often be unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported high recurrence rates despite apparently complete tumor resection and negative postoperative brain imaging, providing another strong argument for the concept of limited surgery combined with other therapeutic approaches, such as radiotherapy or intracystic catheter placement. 2,3,30,37,42,43,50,62,68,71,78,83,84,89,92,98 The surgical routes used to remove craniopharyngiomas have previously been transcranial approaches, whereas the transsphenoidal approach, in accordance with the indications defined by Guiot and Derome 35 in the early 1960s, was proposed initially for infradiaphragmatic lesions, with an enlarged sella, preferably in patients who had already developed panhypopituitarism. 72 More recently, technological progress and advances in terms of visualization permitted the extension of the microscopic transsphenoidal approach to a variety of suprasellar lesions.…”
mentioning
confidence: 99%
“…In particular, clusters of cells with nuclear beta-catenin are predominantly represented in invasive tumors. This pattern is suggestive of an involvement of the beta-catenin signaling in the migratory behavior of these tumors; the cellular clusters with nuclear beta-catenin may coordinate the infiltration of the tumor into surrounding tissues, thus explaining the greater aggressiveness of the adamantinomatous tumor histotype (Hussain et al, 2013;Larkin and Ansorge, 2013).…”
Section: Introductionmentioning
confidence: 92%